KONSEP PENDIDIKAN MENURUT IBNU KHALDUN DALAM KERANGKA PRAGMATIS-INSTRUMENTALIS - Mahmudah, Umi; Mardiatul Hayat; Yuangga Kurnia Yahya (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam UNISMA Bekasi, 2024)
The study aims to analyze Ibn Khaldun's (1332-1404) thoughts on education and relate them to the pragmatic-instrumental perspective initiated by John Dewey (1859-1952), especially to become the basis for innovation in contemporary Islamic education. This study is a qualitative study with data sources from the library. This study concludes that Ibn Khaldun's thinking has educational goals, output, processes and content that overlap with pragmatic education initiated by John Dewey. Another important thing is that the relationship of thought between the two shows that educators and managers of Islamic educational institutions do not need to feel unfamiliar with the instrumental pragmatism approach which is government policy and society's demands. However, as Ibnu Khaldun did, they can formulate innovations in education according to the context of the needs of the times and the basis of Islamic epistemology.